Concrete spherical joint contact stress distribution and overturning moment of swing bridge. (December 2020) - Liu, Tao; Yu, Qingliang; Fan, Jianfeng; Peng, Ziqiang; Wang, Erlei
Abstract: The present study aims to address the instability mode of the concrete spherical joint in order to guarantee the safety of the rotating process of the swing bridge. A new critical overturning moment model is proposed to calculate the overturning moment of swing bridge based on the non-Hertz contact theory, and it is validated against the engineering application of the Nandu River Swing Bridge construction. The research indicates that the Non-Hertz contact theory has superiority compared to the widely applied simplified formulation on the spherical joint surface stress calculation, by contrasting the results of the finite element model and the data collected during field monitoring. Furthermore, the resistance of the overturning coefficient is calculated, and the result turns out that the critical resistance of the overturning coefficient based on the Non-Hertz contact theory is closer to the measured values compared to the simplified algorithm. The present research demonstrates the applicability of applying the new proposed formula to guarantee the safety of the rotating process during the swing bridge construction.